The potential of pamrevlumab in diseases with underlying mechanisms of fibrotic processes and its prospects in ophthalmology - Lely Retno Wulandari; Edwin Damar Prabowo; Happy Kurnia Permata Sari; Hidayat Sujuti; Sri Winarsih (Pharmacia)
Introduction: Pamrevlumab, a monoclonal antibody targeting CTGF, is considered a potential therapy for eye diseases involving fibrosis. The aim of this study was to explore its potential in treating eye diseases. Methods: A systematic review was conducted following PRISMA guidelines, searching studies up to 2024 across various databases. Study quality was assessed using the Cochrane RoB 2.0 tool. Results: Pamrevlumab has the potential to slow fibrosis progression and improve organ function, although treatment responses varied. Two studies showed significant changes, while four did not. The risk of bias indicated varied methodological quality. Discussion: Pamrevlumab shows potential in treating fibrosis-related eye diseases by inhibiting CTGF. Further research is needed to assess its long-term effects, safety, and dose optimization. Conclusion: Pamrevlumab shows significant potential in the treatment of chronic eye diseases, with promising safety outcomes based on previous experiences in DMD patients.